Prevalensi dan komplikasi pada penderita gagal ginjal kronik yang menjalani hemodialisa di Rumah Sakit Umum Pusat Sanglah Denpasar tahun 2018 - Ida Ayu Ari Utami; Desak Gede Diah Dharma Santhi; Anak Agung Wiradewi Lestari (DiscoverSys Inc., 2020)
Background: The prevalence of chronic kidney failure in Australia, Japan and Europe is 6-11%, increased relatively about 5-8% per year. Meanwhile, in Indonesia, the prevalence of chronic kidney failure is 0.2% of total. Only 60% of patients with chronic kidney failure had dialysis therapy.Aim: This study aims to determine the prevalence of patients with chronic kidney failure who do hemodialysis at RSUP Sanglah and to determine the description of complications in patients with chronic kidney failure who do hemodialysis at RSUP Sanglah.Method: This was a categorical descriptive study looking at medical records of chronic renal failure patients do hemodialysis at RSUP Sanglah in 2018 with a sample of 45 patients who had met the inclusion and exclusion criteria. The study sample consisted of chronic kidney failure patients do hemodialysis and complications.Results and conclusion: There were 16 patients with chronic renal failure do hemodialysis at RSUP Sanglah and there were complications consisting of complications of hypertension, hyperuremia, hyperkalemia, metabolic acidosis and anemia. Prevalensi gagal ginjal kronik di negara Australia, Jepang dan Eropa adalah 6 – 11%, terjadi peningkatan 5 – 8% pertahun. Sedangkan, di Indonesia terdapat prevalensi gagal ginjal kronik 0,2% dari penduduk di Indonesia. Hanya 60% dari pasien gagal ginjal kronik yang menjalani terapi dialisis.Tujuan: untuk mengetahui prevalensi pasien gagal ginjal kronik yang melakukan hemodialisis di Rumah Sakit Umum Pusat (RSUP) Sanglah dan untuk mengetahui gambaran komplikasi pada pasien gagal ginjal kronik yang melakukan hemodialisis di RSUP Sanglah.Metode: Penelitian ini merupakan penelitian deskriptif kategorik melihat dari catatan rekam medis pasien gagal ginjal kronik yang menjalani hemodialisis di RSUP Sanglah pada tahun 2018 dengan sampel sebanyak 45 pasien yang telah memenuhi kriteria inklusi dan eksklusi. Sampel penelitian terdiri dari pasien gagal ginjal kronik yang menjalani hemodialisis dan terdapat komplikasi.Hasil dan simpulan: Terdapat 16 pasien gagal ginjal kronik yang menjalani hemodialisis di RSUP Sanglah dan terdapat komplikasi yang terdiri dari komplikasi hipertensi, hiperuremia, hiperkalemia, asidosis metabolik dan anemia.